Case report: Multicentric Castleman disease as a manifestation of immune reconstitution inflammatory syndrome in Malawi - Painschab, Matthew S.; Mponda, Marriam; Tomoka, Tamiwe; Kampani, Coxcilly; Chimzimu, Fred; Fedoriw, Yuri; Gopal, Satish (Frontiers in Oncology, 2022)
Introduction: Multicentric Castleman disease (MCD) is a lymphoproliferative disorder characterized by systemic inflammation, lymphadenopathy, and cytopenias. MCD caused by Kaposi sarcoma herpesvirus (MCD-KSHV) frequently arises in the context of HIV. It can be associated with immune reconstitution inflammatory syndrome (IRIS), but MCD-IRIS is rarely reported in sub-Saharan Africa (SSA) where HIV and KSHV infection are common. Case description: A 36-year-old woman in Malawi with HIV on antiretroviral therapy (ART) for nine years presented with fatigue, weight loss, and lymphadenopathy. Lymph node biopsy was consistent with HIV lymphadenitis without evident KSHV-MCD and HIV RNA was 4,244 copies/mL. She switched to second-line ART and returned four months later with worsening lymphadenopathy, fever, night sweats, weight loss, and anemia. A repeat lymph node biopsy demonstrated unequivocal KSHV-MCD features not present on the original biopsy. Her repeat HIV viral load was undetectable and she received chemotherapy with subsequent remission on continued ART for >24 months. Discussion: This is among the first reported cases of MCD-IRIS from SSA, which has implications for a region where HIV and KSHV are highly prevalent. MCD-IRIS may contribute to early mortality after ART initiation in SSA, and increased awareness alongside improved diagnostic and treatment capacity are needed.